Feasibility of an Electrostatic Energy Harvesting Device for CFCs Aircraft. (2015) - Xie, Huiling; Huang, Zhaorong; Guo, Shijun; Torru, Ekiyor
Abstract: A novel energy harvesting concept is proposed for treating local electrostatic energy produced on flying composite aircrafts. This work focuses on the feasibility research on collecting static charges with capacitive collectors. The existing energy harvesting system and the electrification of the typical carbon fibre composites (CFCs) aircraft has been reviewed. The detailed model experiments were then designed to characterize different configurations for electrostatic energy harvesting on aeroplane. In the lab, the static charge was produced by a corona discharging device, and a capacitor or a metal sheet was put in the electric field to collect the charges under four different configurations. After that, the rest results for these configurations were analysed, which is followed by the discussion about the results application on the aircraft. This work has proved that it is feasible to collect the local static electricity on flying aircraft, and it could provide a new direction of energy harvesting system in aviation field.